Clinical Characteristics of De Novo Heart Failure and Acute Decompensated Chronic Heart Failure: Are They Distinctive Phenotypes That Contribute to Different Outcomes? - Wilson Matthew Raffaello (Radcliffe Medical Media, 2021)
Heart failure is currently one of the leading causes of morbidity and mortality. Patients with heart failure often present with acute symptoms and may have a poor prognosis. Recent evidence shows differences in clinical characteristics and outcomes between de novo heart failure (DNHF) and acute decompensated chronic heart failure (ADCHF). Based on a better understanding of the distinct pathophysiology of these two conditions, new strategies may be considered to treat heart failure patients and improve outcomes. In this review, the authors elaborate distinctions regarding the clinical characteristics and outcomes of DNHF and ADCHF and their respective pathophysiology. Future clinical trials of therapies should address the potentially different phenotypes between DNHF and ADCHF if meaningful discoveries are to be made.